2012
DOI: 10.5601/jelem.2012.17.2.15
|View full text |Cite
|
Sign up to set email alerts
|

The role of magnesium in migraine pathogenesis. Potential use of magnesium compounds in prevention and treatment of migraine headaches

Abstract: One of the major functions of magnesium is the maintenance of proper electric potential of neurons. Pathological conditions associated with systemic magnesium deficiencies may be associated with disturbance of numerous neurophysiological processes. These may include neuron function, transmission of nerve impulses, neuromuscular transmission, muscle contraction and vasomotor reflex. Therefore, magnesium deficiencies, particularly those associated with hypomagnesemia, are a source of problems for neurologists. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…Mg 2+ deficiency may contribute to migraine attacks in multiple ways including regulation of calcium ion influx, serotonin receptor activity, platelet aggregation, cerebrovascular tone, and release of nitric oxide and inflammatory mediators such as neuropeptides, substance P, and cytokines. 14,34 These broad neurovascular, neuropeptide, and transmitter actions of Mg 2+ clearly overlap with known migraine pathogenesis. 14,34,35 Nevertheless, a direct link between Mg 2+ deficiency and MRM is yet to be demonstrated.…”
Section: Magnesium (Mg 2+mentioning
confidence: 95%
See 2 more Smart Citations
“…Mg 2+ deficiency may contribute to migraine attacks in multiple ways including regulation of calcium ion influx, serotonin receptor activity, platelet aggregation, cerebrovascular tone, and release of nitric oxide and inflammatory mediators such as neuropeptides, substance P, and cytokines. 14,34 These broad neurovascular, neuropeptide, and transmitter actions of Mg 2+ clearly overlap with known migraine pathogenesis. 14,34,35 Nevertheless, a direct link between Mg 2+ deficiency and MRM is yet to be demonstrated.…”
Section: Magnesium (Mg 2+mentioning
confidence: 95%
“…14,34 These broad neurovascular, neuropeptide, and transmitter actions of Mg 2+ clearly overlap with known migraine pathogenesis. 14,34,35 Nevertheless, a direct link between Mg 2+ deficiency and MRM is yet to be demonstrated. Herein, we suggest that Mg 2+ deficiency is a critical factor in modulating OT/ OTR signaling that leads to an increased likelihood of MRM.…”
Section: Magnesium (Mg 2+mentioning
confidence: 95%
See 1 more Smart Citation
“…Previous documents reported that migraine patients may have magnesium deficiency and also low brain magnesium during attacks ( 61 , 62 ). In addition, previous studies proposed the reduction of prostacyclin-dependent vasodilation, blocking of N-Methyl-D-aspartate (NMDA) receptors, and inhibition of serotonin-dependent vascular spasm as possible mechanisms of magnesium in the context of migraine prevention ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…These alterations have been proposed to decrease neurons' resting potential and reduce their threshold for action potentials (46) . Conversely, Mg has been proposed to prevent migraine by blocking N-Methyl-D-aspartate (NMDA) receptors, inhibiting serotonin-dependent vascular spasm, and reducing prostacyclindependent vasodilation (47) . The DASH diet contains no to low amounts of processed meats, refined grains, and fried foods, all of which have been associated with higher migraine complications or frequency (48) .…”
Section: Discussionmentioning
confidence: 99%